Implementasi Perawatan untuk Orang yang Telah Meninggal oleh Tarjih dan Tajdid Muhammadiyah Bantul - Chusnul Azhar; Yunita Furi Aristyasari (Universitas Muhammadiyah Sidoarjo, 2020)
This study aims to know the practice of corpse care at PKU Muhammadiyah Hospi- tal Bantul to get conclusions about the suitability of its application with the guidance of the Tarjih and Tajdid Muhammadiyah Council. To get a complete picture of the corpse care process at PKU Muhammadiyah Hospital Bantul, researchers used data collection techniques with observation, interviews, and documentaries. The results of this study concluded that the practice of bathing and kafiaing corpses in the PKU Muhammadiyah Bantul Hospital was in accordance with the guidance of the Tarjih and Tajdid Muham- madiyah Central Management Council. Inthis study it was also found that there was no guidance from the Tarjih and Tajdid Muhammadiyah Council on the handling of bathing the corpses that were indicated as having infectious diseases. Thus, there is a need for a comprehensive new perspective in looking at the problems that arise in the midst of the people along with the times.